Fifty years of slavery in the United States of America by Harry Smith. - Smith, Harry, 1815?- (West Michigan Print. Co., 1891)
Smith's narrative relates not only his personal experiences, but also includes many anecdotes about other Kentucky slaves and masters. Many of his stories are humorous and pleasant, relating to sporting adventures and leisure activities. Others, however, relate instances of neglect, violence, and the mistreatment of slaves by their masters and other white authorities. Although Smith's narrative focuses primarily on slave family life on large plantations, it also highlights the interactions between whites and blacks, and the dynamics of those relationships.
"A Clark Historical Library Reprint"
A narrative of slave life in Kentucky.
Keywords: Smith, Harry, -- 1815?-; Enslaved persons -- Personal narratives.; Enslaved persons -- Kentucky -- Biography.; Slavery -- Kentucky.; Slavery -- United States.; Plantation life -- Kentucky.; Enslaved persons -- Kentucky -- Social life and customs.; Enslaved persons' writings, American -- Kentucky.; Plantation life.; Slavery.; Enslaved persons.; Enslaved persons -- Social life and customs.; Enslaved persons' writings, American.; Kentucky.; United States.; Biographies.; Personal narratives.